The Shift from the Death Penalty to Imprisonment for Juveniles: An Analysis of Injustice from the Perspective of Existentialist Philosophy - Kevin Wibisana; Angkasa Angkasa (CV. Publikasi Indonesia, 2026)
This study examines procedural failures in the imposition of the death penalty on a child that was later commuted to imprisonment, as reflected in the Decision of the Gunungsitoli District Court Number 8/Pid.B/2013/PN-GST and the Supreme Court Judicial Review Decision Number 96 PK/Pid/2016. The central issue of this research lies in the erroneous verification of the defendant’s age, which resulted in a child being treated as an adult and sentenced to death, contrary to Law Number 11 of 2012 on the Juvenile Criminal Justice System and the principles of child protection. This research aims to analyze the procedural failure, explain its juridical and ethical implications, and critically assess practices of dehumanization in juvenile criminal law through the existentialist perspectives of Jean-Paul Sartre and Albert Camus. The study employs a normative legal research method with a qualitative approach, utilizing statutory, case, and legal philosophy approaches, supported by library research on court decisions and existentialist literature. The findings indicate that an excessively formalistic and positivistic application of law has negated the recognition of children as human subjects in the process of becoming, resulting in procedural and existential injustice. This research concludes that child protection in criminal law cannot be understood merely in normative terms but must be grounded in ethical and existential awareness to realize a more humanistic juvenile criminal justice system.